Perjalanan Politik Birokrasi Di Indonesia : (Kajian Teori dan Analisis Konsep) - La Ode Wahiyuddin (Program Studi Ilmu Pemerintahan, Universitas Muhammadiyah Kendari, 2022)
The purpose of this writing is to describe the political journey of bureaucracy in Indonesia. The research method used is a literature review with Systematic Review Technique by viewing and identifying existing problems by developing existing concepts. The results of the study indicate that politics are very dominant in influencing bureaucratic activities and activities. Bureaucracy tends to be coopted on the interests of political officials, so that they want to not want to follow the will of political officials. The presence of Law Number 43 of 1999 to the main principal of civil servants put political officials more dominant in determining the bureaucratic career. In line with that, the presence of Law Number 5 of 2014 concerning the Civil Apparatus of the State Place the position in accordance with merit toxration but it also has not been implemented optimally. The influence of political officials is still very dominant in determining bureaucratic positions. Keywords: Politics, Bureaucracy, Indonesia